Development spotlight - Ukraine, a model of success - Digel, H. (New Studies in Athletics, 2011)
The Ukraine can look back on a long and glorious tradition in athletics. As a part of the Soviet Union it supplied many of that country`s famous victories, most notably those by Olympic champions Valeriy Borzov and Sergey Bubka, both of whom are presently in leading positions in Ukrainian sport organisations.